Innovative Medicine 2015
DOI: 10.1007/978-4-431-55651-0_17
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels: Their Function and Potentiality as Drug Targets

Abstract: The transient receptor potential (TRP) proteins are a family of ion channels that act as cellular sensors as well as signal integrators. Several members of the TRP family are sensitive to changes in cellular redox status. Among them, TRPA1 is remarkably susceptible to various oxidants and is known to mediate neuropathic pain and respiratory, vascular, and gastrointestinal functions, making TRPA1 an attractive therapeutic target. However, a method to achieve selective modulation of TRPA1 by small molecules has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 170 publications
0
15
0
1
Order By: Relevance
“…TRP channels respond well to oxidative stress mediators such as: reactive oxygen species (ROS), reactive nitrogen species (RNS) and other electrophiles. The transient receptor potential melastatin-2 (TRPM2) channel, which is the fi rst identifi ed ROS sensitive channel, is activated by hydrogen peroxide (H 2 O2) and is the mediator of numerous cellular responses including cell death and chemokine production (4). It has been reported that TRPM2 channels have crucial effects on migration and cell death in tumour cells and immune system cells and its expression is enhanced significantly in adenocarcinomas such as: breast cancer, head and neck, bladder, liver, pancreas, colon and lung adenocarcinomas (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…TRP channels respond well to oxidative stress mediators such as: reactive oxygen species (ROS), reactive nitrogen species (RNS) and other electrophiles. The transient receptor potential melastatin-2 (TRPM2) channel, which is the fi rst identifi ed ROS sensitive channel, is activated by hydrogen peroxide (H 2 O2) and is the mediator of numerous cellular responses including cell death and chemokine production (4). It has been reported that TRPM2 channels have crucial effects on migration and cell death in tumour cells and immune system cells and its expression is enhanced significantly in adenocarcinomas such as: breast cancer, head and neck, bladder, liver, pancreas, colon and lung adenocarcinomas (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Transient receptor potential (TRP) protein was fi rst identifi ed in Drosophila trp genes in 1989 (5). The TRP protein family contains different groups of calcium ion (Ca 2+ ) permeable and non-selective cation channels and is found in many living organisms (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…There are 6 subtypes of TRP channels; TRPC (canonical), TRPV (vanilloid), TRPM (melastatin), TRPP (polycystic kidney disease), TRPML (mucolipin) and TRPA (ankyrin) TRP channels contain tetrameric subunit stoichiometry and each subunit contains cytoplasmic N and C-terminal regions, 6 transmembrane (TM) domains, and TM5-TM6 interspaces (9). TRP channels are responsive to stimuli such as receptor stimulation, heat, plantderived compounds, environmental irritants, mechanical stress, pH, intra-and extracellular voltage, and respond physiologically and pathologically (5,6,(7)(8)(9)(10). In addition, TRP channels respond fairly well to oxidative stress mediators such as: reactive oxygen species (ROS), reactive nitrogen species (RNS), and other electrophiles (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karakteristik (232) dari Kalsium Klorida merupakan memiliki 3 struktur (73) kristal yaitu ortorombik, tetragonal, dan trigonal. Kalsium klorida boleh berfungsi sebagai sumber ion (74)(75)(76)(77)(78) kalsium dalam larutan aqua kerena sifat kalsium klorida yang boleh larut dalam air. Sifat (79) ini berguna untuk mengeluarkan ion daripada larutan (80) .…”
unclassified